Investigation of physical activity levels by gender and residential areas: a case study on students in Akdeniz University - PINAR, SALİH; PINAR, YELİZ (ELSEVIER SCIENCE BV, 2012)
Problem Statement: The promotion of a healthy lifestyle is the main goal of physical education in many countries. However, very little is known about the relationship between different residential areas and physical activity patterns among young people. Purpose of Study: To compare the physical activity levels (PAL) of university student in accordance with gender (male, n=250; female, n=200) and residential areas (in campus; n=196 and out of campus; n=254). Methods: This study included a total of 450 voluntary healthy subjects (21.04 +/- 1.61 years old) from two different residential areas. PAL's of students were evaluated by using the long form International Physical Activity Questionnaires. BMI was computed as kg/m(2). Data from the questionnaires was collected in a suitable relational database and analyzed with statistical software. The independent-samples t test was applied to understand differences in Physical Activity (PA) levels in terms of genders and also their residential areas. Results: Total PAs (MET min./week) of male students were higher than female counterparts (p<.01). On the other hand, PA at home or in garden domains of female students were higher than male counterparts (p<.05). It was observed that male students walk more and performed more moderate activities (MPA) than female counterparts (p<.01). When their residential areas were taken into consideration, students living in their own house had higher total PA (MET min./week) and higher MPA than students living in dormitory (p<.01). Conclusion: This study showed that PAL is higher for male students than female counterparts as indicated in the current literature. On the other hand, living far distant from campus played important role in having higher PAL in this study. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Physical Activity; IPAQ; MET; PREDICTORS; OBESITY